The - Kuzmeski, Maribeth
In today's commoditized marketplace, no matter what product or service you sell, there's probably someone somewhere able to offer it cheaper, faster, and maybe even better. So how do you differentiate yourself from your competitors? The Connectors shows that the only thing that truly sets you apart is the quality of your relationships with your clients and customers. Everyone knows that relationships are important in business. Yet most people would admit that their relationships could be better—but don’t spend time working on the underlying skills. This book explains how to develop better, more profitable connections—as illustrated proven by some of the world’s most successful professionals. Even if you're not a “people person,” you can dramatically grow your business or your career through a few simple approaches to relationship-building